CONCEPTUAL FRAMEWORK OF SAFETY LEADERSHIP RELATIONSHIP TO SAFETY CULTURE IN INCREASING SAFETY PERFORMANCE OF CONSTRUCTION PROJECTS - Tri Rachma Sari; Rossy Armyn Machfudiyanto; Leni Sagita Riantini (International Journal Labs, 2022)
The construction industry is still one of the biggest contributors to the number of accidents in Indonesia, this explains the low safety performance in construction projects. The low safety performance is proof that safety has not become a priority and has not become a culture. The maturity level of safety culture in the construction industry is at a reactive level, which means it is still very low and efforts need to be made to continuously improve it. The results of the literature study state that there are several efforts that can be made to improve safety culture, namely in terms of leadership, safety behavior, safety planning, individual capabilities, and reporting and evaluation. Safety leadership has the greatest role in enhancing safety culture. Safety leadership is part of a leadership system which is defined as the process of interaction of leaders with followers to achieve safety. Improved safety culture can improve safety performance on construction projects. The purpose of this study was to determine the variables and indicators of safety leadership that can be a part of improving safety culture and the variables and indicators that are used to measure safety performance. The results of these indicators are expected to be a concern for improvement and references to improve safety culture and affect the safety performance of construction projects, so as to reduce the number of accidents in construction projects.